A solution-based ALD route towards (CH3NH3)(PbI3) perovskite via lead sulfide films - Koch, Vanessa; Barr, Maissa; Büttner, Pascal; Mínguez-Bacho, Ignacio; Döhler, Dirk; Winzer, Bettina; Reinhardt, Elisabeth; Segets, Doris; Bachmann, Julien (Journal of Materials Chemistry A, 2019)
We present a procedure to grow thin films of lead sulfide (PbS) with 'solution Atomic Layer Deposition' (sALD), a technique which transfers the principles of ALD from the gas phase (gALD) to liquid processing. PbS thin films are successfully deposited on planar and porous substrates with a procedure that exhibits the unique ALD characteristics of self-limiting surface chemistry and linear growth at room temperature. The polycrystalline p-type PbS films are stoichiometric and pure. They are converted to the hybrid perovskite methylammonium iodoplumbate (methylammonium lead iodide, MAPI, CH3NH3PbI3) by annealing to 150 °C in the presence of vapors from methylammonium iodide (MAI).
CRIS-Team Scopus Importer:2019-11-19

From Sticky to Slippery: Self-Functionalizing Lubricants for in Situ Fabrication of Liquid-Infused Surfaces - Chiera, Salvatore; Koch, Vanessa; Bleyer, Gudrun; Walter, Teresa; Bittner, Carina; Bachmann, Julien; Vogel, Nicolas (ACS Applied Materials and Interfaces, 2022)
Liquid-infused surfaces offer a versatile approach to create self-cleaning coatings. In such coatings, a thin film of a fluid lubricant homogeneously coats the substrate and thus prevents direct contact with a second, contaminating liquid. For stable repellency, the interfacial energies need to be controlled to ensure that the lubricant is not replaced by the contaminating liquid. Here, we introduce the concept of self-functionalizing lubricants. Functional molecular species that chemically match the lubricant but possess selective anchor groups are dissolved in the lubricant and self-adhere to the surface, forming the required surface chemistry in situ from within the applied lubricant layer. To add flexibility to the self-functionalizing concept, the substrate is first primed with a thin polydopamine base layer, which can be deposited to nearly any substrate material from aqueous solutions and retains reactivity toward electron-donating groups such as amines. The temporal progression of the in situ functionalization is investigated by ellipsometry and quartz crystal microbalance and correlated to macroscopic changes in contact angle and contact angle hysteresis. The flexibility of the approach is underlined by creating repellent coatings with various substrate/lubricant combinations. The prepared liquid-infused surfaces significantly reduce cement adhesion and provide easy-to-clean systems under real-world conditions on shoe soles.
CRIS-Team Scopus Importer:2022-04-22
Keywords: coatings; liquid-infused surfaces; polydopamine; self-cleaning; surface functionalization

Mechanistic Insight into Solution-Based Atomic Layer Deposition of CuSCN Provided by In Situ and Ex Situ Methods - Hilpert, Felix; Liao, Pei-Chun; Franz, Evanie; Koch, Vanessa; Fromm, Lukas; Topraksal, Ece; Görling, Andreas; Smith, Ana-Suncana; Barr, Maissa; Bachmann, Julien; Brummel, Olaf; Libuda, Jörg (ACS Applied Materials and Interfaces, 2023)
Solution-based atomic layer deposition (sALD) processes enable the preparation of thin films on nanostructured surfaces while controlling the film thickness down to a monolayer and preserving the homogeneity of the film. In sALD, a similar operation principle as in gas-phase ALD is used, however, with a broader range of accessible materials and without requiring expensive vacuum equipment. In this work, a sALD process was developed to prepare CuSCN on a Si substrate using the precursors CuOAc and LiSCN. The film growth was studied by ex situ atomic force microscopy (AFM), analyzed by a neural network (NN) approach, ellipsometry, and a newly developed in situ infrared (IR) spectroscopy experiment in combination with density functional theory (DFT). In the self-limiting sALD process, CuSCN grows on top of an initially formed two-dimensional (2D) layer as three-dimensional spherical nanoparticles with an average size of ∼25 nm and a narrow particle size distribution. With increasing cycle number, the particle density increases and larger particles form via Ostwald ripening and coalescence. The film grows preferentially in the β-CuSCN phase. Additionally, a small fraction of the α-CuSCN phase and defect sites form.<br
Keywords: solution atomic layer deposition; liquid phase; in situ IR spectroscopy; atomic force microscopy; copper thiocyanate; neural network; density functional theory

Sb2Se3Thin-Film Growth by Solution Atomic Layer Deposition - Koch, Vanessa; Charvot, Jaroslav; Cao, Yuanyuan; Hartmann, Claudia; Wilks, Regan G.; Kundrata, Ivan; Minguez Bacho, Ignacio; Gheshlaghi, Negar; Hoga, Felix; Stubhan, Tobias; Alex, Wiebke; Pokorný, Daniel; et al. (Chemistry of Materials, 2022)
We establish solution atomic layer deposition (sALD) for the controlled growth of pure Sb2Se3 thin films under mild conditions, namely, room temperature and atmospheric pressure. Upscaling this process yields Sb2Se3 thin films with high homogeneity over large-area (4″) substrates. Annealing of the initially amorphous material leads to highly crystalline and smooth Sb2Se3 thin films. Removing the constraints of thermal stability and sufficient volatility in sALD compared to traditional gas-phase ALD opens up a broad choice of precursors and allows us to examine a wide range of Se2- precursors, of which some exhibit facile synthetic routes and allow us to tune their reactivity for optimal experimental ease of use. Moreover, we demonstrate that the solvent used in sALD represents an additional, attractive tool to influence and tailor the reactivity at the liquid-solid interface between the precursors and the surface.
Created from Fastlane, Scopus look-up

Spray-Drying and Atomic Layer Deposition: Complementary Tools toward Fully Orthogonal Control of Bulk Composition and Surface Identity of Multifunctional Supraparticles - Müssig, Stephan; Koch, Vanessa; Cuadrado, Carlos Collados; Bachmann, Julien; Thommes, Matthias; Barr, Maissa; Mandel, Karl (Small Methods, 2021)
Spray-drying is a scalable process enabling one to assemble freely chosen nanoparticles into supraparticles. Atomic layer deposition (ALD) allows for controlled thin film deposition of a vast variety of materials including exotic ones that can hardly be synthesized by wet chemical methods. The properties of coated supraparticles are defined not only by the nanoparticle material chosen and the nanostructure adjusted during spray-drying but also by surface functionalities modified by ALD, if ALD is capable of modifying not only the outer surfaces but also surfaces buried inside the porous supraparticle. Simultaneously, surface accessibility in the porous supraparticles must be ensured to make use of all functionalized surfaces. In this work, iron oxide supraparticles are utilized as a model substrate as their magnetic properties enable the use of advanced magnetic characterization methods. Detailed information about the structural evolution upon individual ALD cycles of aluminium oxide, zinc oxide and titanium dioxide are thereby revealed and confirmed by gas sorption analyses. This demonstrates a powerful and versatile approach to freely designing the functionality of future materials by combination of spray-drying and ALD.
CRIS-Team Scopus Importer:2021-12-03
Keywords: atomic layer deposition; spray-drying; supraparticles